Chapter 4 Forever small? A longue durée perspective on Luxembourg's extantism, governance, and security - Kolnberger, Thomas (Taylor & Francis, 2024)
Luxembourg is a prototypical small state and the only remaining example of over a two dozen of grand duchies in history. In this chapter the focus is laid on persistency and change of governance in security aﬀairs, that is, the question of how a Luxembourg political entity overcame a variety of challenges of the (European) security environment until 1940. Indeed, to comprehend the 'survival' of the Grand Duchy in face of the vicissitudes of the military-political setting since the princedom's creation by the Treaty of Vienna (1815), one needs to deploy the full array of the Small-State theory debate in security policy and in the politics of international relations: bandwagoning, balancing, freeriding, hedging, shelter-seeking. Based on this longue durée approach, the contribution expands on 'extantism' to reintroduce this concept to Small-State Studies.